Efektivitas Metode ABA Dalam Meningkatkan Keterampilan Interaksi Sosial Pada Anak Autis - Hapsari, Frida Lolita; Ardani, Tristiadi Ardi (CV. Lentera Literasi Indonesia, 2025)
According to the CDC, the latest data for children with autism in 2024 is 1 in 36 children. Approximately 2.4 million youngsters are predicted to have autism by 2024, according Dr. Dante, Deputy Minister of Helath. The complex illness known ad Autism Spectrum Disorder affects behavior, socialization, communication, and sensory/cognitive. This article’s goal is to determine how well ABA therapy works in improving the social interaction skills of children with autism, including their preference for playing alone or with objects without friends and their lack of interest in social. This study’s methodology is literature research. The findings demonstrated that the application of therapy with ABA methods can significantly and effectively improved the social interacton skills of children with autism.